Interactivity as a Retention Factor in Learning Biology Through the Protégé Effect - Malik Pelumi, Bello; Adeyinka Oluwaseun, Kareem; Folorunsho Emmanuel, Bamidele (Journal of Teaching and Learning, 2025)
This study investigated the role of interactivity on the protégé effect, and explored how biology teachers can utilize it in their classrooms to reduce rote learning and facilitate long-term retention. This investigation utilized the generative learning theory, and adopted a non-equivalent quasi- experimental research design involving 60 students. The instruments used for this study include a stimulus instrument titled, Teachers’ Instructional Guide on Ecology of Population (TIGEP), which was used as guide for teaching ecology with the protégé effect, and three response instruments. The first, the Population Ecology Requirement Test (PERT), was used to show the required knowledge for the respondents on the protégé effect, while the second and third, the Population Ecology Achievement Tests (PEATs; version 1 and 2), helped to assess the learners’ performances. Results, obtained using analysis of covariance and Bonferroni post-hoc analysis, indicated that the protégé effect significantly influenced the performances of students on immediate tests (Fcal = F(3,55) = 24.47 > Ftab = 8.57, p < 0.001) and on the long-term retention of Biology concepts (Fcal = F(3,55) = 16.25 > Ftab = 8.57, p < 0.001). This study showed that interactivity, via the protégé effect, provides a strong indication for improving academic performance and retention of learned concepts in biology, as it assists in consolidating and integrating learned concepts.